EXPLORING THE COGNITIVE DIMENSIONS OF LANGUAGE ACQUISITION - Chubaryan, Astghik; Vardanyan, Mariam (Armenian Folia Anglistika, 2024)
Cognitive Linguistics, as an expanding discipline in language study, delves into language as a mental phenomenon, presenting a holistic approach that integrates linguistic and cognitive elements. Unlike traditional linguistics, which scrutinizes syntactical patterns, word structures, grammar rules, phonology, semantics, and lexical meanings, Cognitive Linguistics offers a comprehensive model that interweaves various closely connected theories. This study seeks to elucidate the manifestations of Cognitive Linguistics in language, providing scholars with a discerning analysis of existing theories. Furthermore, employing methods of descriptive and comparative analysis, this study aims to demonstrate the impact of Cognitive Linguistics on language processing and acquisition. It highlights its significance in second language acquisition while elucidating the underlying mental processes involved. The paper offers a succinct overview of this evolving discipline, encapsulating its unique characteristics within the encompassing term Cognitive Linguistics.
Keywords: Cognitive Linguistics; cognitive models; mental processes; language processing and acquisition; usage-based theory